An interdisciplinary approach to ensure adherence to exercise and potentially reduce adverse cardiac events in cancer patients: primers in cardio-oncology - Wernhart, Simon; Fiorentini, Caterina; Madl, Bernadine; Kuehberger, Louisa; Glowka, Simon; Murr, Elena; Grill, Sabine; Kiechle, Marion; Alguel, Hana; Bassermann, Florian; Combs, Stephanie E.; Gschwend, Juergen E.; et al. (Frontiers in Oncology, 2025)
Exercise training can improve mortality, quality of life, exercise capacity and morbidity in cancer patients. Although current cardio-oncological guidelines recommend exercise intervention in cancer patients, a structured, interdisciplinary approach from diagnosis to maintenance of therapy including repetitive sports cardiological assessment to guide exercise intervention has not been established. Currently, exercise prescriptions are based on assessment of peak oxygen consumption, which does not differentiate between central (stroke volume and heart rate reserve) and peripheral (peripheral oxygen difference) limitations. Knowledge of these mechanisms could facilitate more effective exercise prescriptions because cancer subtypes may respond differently to exercise stimuli requiring individualized and cancer-specific exercise intervention. Our approach uses simultaneous cardiopulmonary exercise testing and stress echocardiography to analyze the entire oxygen cascade in one exam. Based on these findings, we propose individualized assessment of treatment and cardiovascular risk as well as exercise prescriptions. As cardiopulmonary limitations indicative of cancer therapy-related cardiac dysfunction or cardiotoxicity may first be detected during exercise, our approach may help to address cancer therapy-related adverse events earlier. Our approach contains repetitive exercise testing which should serve to re-assess efficacy of exercise intervention. Results of each sports cardio-oncological assessment is fed back to the treating oncologists as it may provide valuable insights to adapt treatment regimens. In addition, we propose a transition from supervised on-site and home-based to self-directed training, which may achieve better long-term training adherence from prehabilitation to post-treatment. In the advent of precision medicine and oncology we provide a concept for precision sports cardio-oncological care to tailor individual exercise prescriptions based on pathophysiological findings during exercise testing.